2012
DOI: 10.1021/ja302177z
|View full text |Cite
|
Sign up to set email alerts
|

On Ni Catalysts for Catalytic, Asymmetric Ni/Cr-Mediated Coupling Reactions

Abstract: The importance of the Ni catalyst in achieving catalytic asymmetric Ni/Cr-mediated coupling reactions effectively is demonstrated. Six phenanthroline-NiCl(2) complexes 1a-c and 2a-c and five types of alkenyl iodides A-E were chosen for the study, thereby demonstrating that these Ni catalysts display a wide range of overall reactivity profiles in terms of the degree of asymmetric induction, geometrical isomerization, and coupling rate. For three types of alkenyl iodides A-C, a satisfactory Ni catalyst(s) was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
1
27
0
1
Order By: Relevance
“…A stoichiometric reaction of allyl carbonate, benzaldehyde and Ni 0 -L n in the absence of Zn was able to produce the product in a similar yield and ee to the catalytic conditions, suggesting allyl-Ni may be the key intermediate for the allylation event. This is distinctive from the Nozaki-Hiyama-Kishi reactions [84]. In addition, the 1-or 3-phenyl-substituted allyl carbonate gave the product in moderate yield and ee at -25°C but with high anti/syn selectivities.…”
Section: Addition Of Allyl and Benzyl Groups To Carbonyl Compoundsmentioning
confidence: 72%
“…A stoichiometric reaction of allyl carbonate, benzaldehyde and Ni 0 -L n in the absence of Zn was able to produce the product in a similar yield and ee to the catalytic conditions, suggesting allyl-Ni may be the key intermediate for the allylation event. This is distinctive from the Nozaki-Hiyama-Kishi reactions [84]. In addition, the 1-or 3-phenyl-substituted allyl carbonate gave the product in moderate yield and ee at -25°C but with high anti/syn selectivities.…”
Section: Addition Of Allyl and Benzyl Groups To Carbonyl Compoundsmentioning
confidence: 72%
“…Recently, Kishi and co-workers studied the influence of the Ni II source on the addition of (Z)-disubstituted alkenyl iodide 176 to 171 (Scheme 77). [176] They found that the coupling required less than two hours when [{(Me) 3…”
Section: Methodsmentioning
confidence: 99%
“…The use of ligand 138, which contains binding sites for both metals and thus places them in proximity, allowed significant reductions in both the amount of chromium used (1-2 mol %) and the molar ratio of the coupling partners (171/ 172 1:1 to 1:1.1). [176] They found that the coupling required less than two hours when [{(Me) 3 [172] The great efficiency of these new ligands has been demonstrated in the total synthesis of various challenging natural products and intermediates, [173] including building blocks of E7389 and halichondrin B/C [174] (Figure 6 and Schemes 74 and 75) as well as aplyrorine A-mycalolide B hybrid compound [175] (Figure 6, Recently, Kishi and co-workers studied the influence of the Ni II source on the addition of (Z)-disubstituted alkenyl iodide 176 to 171 (Scheme 77).…”
Section: Asymmetric Synthesis Of Allylic Alcoholsmentioning
confidence: 99%
“…2,9-Dimethyl-4,7-bis(oct-7-enyloxy)-1,10-phenanthroline (3) was synthesized as shown below, adapting a literature procedure. [31] The NaH dispersion in mineral oil was washed with hexane immediately prior to use. THF was distilled from sodium and benzophenone.…”
Section: Methodsmentioning
confidence: 99%